Conflitos enfrentados pela população de gambás-de-orelha-preta, Didelphis aurita (Wied-Neuwied, 1826), em áreas urbanizadas - Macedo, Iasmin (2023)
Native wildlife animals are suffering due to habitat loss and need to seek new areas to survive. Cities have become an option for the survival of these animals, with abundant food and shelter available. Some species have adapted very well to the point where their population density is higher in urban areas than in natural ones, referred to as 'urban exploiters.' The interaction between humans and wildlife increases, leading to both benefits and conflicts. This study aimed to identify and characterize conflicts affecting the well-being and health status of the population of the Black-Eared Opossums, Didelphis aurita (Wied-Neuwied, 1826), in an urban area in the state of Espírito Santo. Initially, an analysis of data from rescues in 2022 was conducted through a systematic study implemented at the Wildlife Rehabilitation Center in the state of Espírito Santo (CETAS/IBAMA/ES). The inspection of the rescued individuals was carried out or handed over for the detection of mites and ticks. Finally, the outcomes of the animals attended to were reported, showing the success rate in rehabilitating these animals. In the year 2022, 144 cases of rescues were recorded, which included 421 individuals of D. aurita at CETAS/IBAMA/ES. Only 19 could be released immediately, while the rest required care. The conflict with the highest number of occurrences was orphaned pups (N = 78), which resulted in more effort in caring for the individuals (N = 339). Moreover, many individuals (N = 209) were received in a short period, between September and October 2022, which was corresponds to the species' reproductive period. No mites or ticks were detected in the evaluated D. aurita individuals (16 adults, 14 juveniles, 102 medium-sized offspring, and 32 small offspring). Despite efforts, only 131 individuals could be released, and the other 290 died or were euthanized. The arrival of orphaned individuals as the most frequent conflict, intensified in the months of September and October, causing an overload of interventions, raises an alert regarding the impact on adult females and the need to invest resources and attention in the survival of offspring. Environmental education within the community in regions where these conflicts occur and/or in proximity to the months preceding the species' reproductive period, is crucial for reducing these conflicts and, consequently, decreasing the admissions to rehabilitation centers. The results shed light on the dynamics of these conflicts and can be explored to investigate aspects of the interaction between humans and native wildlife, as well as the community's perception of the importance of these animals.